PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V UPTD SD NEGERI 28 PAREPARE - Ritha Tuken; Kamaruddin Hasan; Rista Sasmitha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the improvement of students' learning process and activity through the applying of the Problem Based Learning (PBL) learning model. This research uses a qualitative approach and the type of research used is Classroom Action Research (PTK). The focus of the research is the focus of the learning process and the focus of activeness. This research was carried out at UPTD SD Negeri 28 Parepare for the 2024/2025 school year with the subject of this study, namely 1 class teacher and 30 students consisting of 15 male and 15 female. The research was carried out in two cycles, each of which consisted of two meetings which included planning, implementation, observation, and reflection. The data collection techniques used are process observation, active observation, and documentation. The data was analyzed using data condensation techniques, data presentation, and conclusion drawn. In the first cycle, the results of the study showed that the learning process of teacher and student activities was in the category Enough (C). Then, the students' learning activity is at a moderate qualification level. The second cycle shows that the learning process of teacher and student activities is in the Good (B). Then, the students' learning activity is at a high qualification level. So it can be concluded that by applying the Problem Based Learning (PBL) learning model in the subject of Pancasila Education, it can improve the learning process and learning activity of students in class V UPTD SD Negeri 28 Parepare.